Pengaruh Mind Mapping terhadap Kemampuan Pemahaman Baca Siswa di SD/MI - Nur Ihwanul Karim; Ayu Novirianti; Ika Putra Viratama (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the impact of mind mapping on reading comprehension skills among elementary school students (SD/MI). In this journal, the approach used is a literature review by analyzing various relevant sources related to the influence of mind mapping on reading comprehension skills in SD/MI. This method aims to collect, evaluate, and summarize existing information in the literature, including journal articles, books, and credible online sources. The results of the analysis indicate that students who utilize mind mapping experience a significant improvement in their reading comprehension abilities. These findings suggest that mind mapping can be an effective strategy for enhancing students' reading comprehension by helping them organize information visually and facilitating a more interactive learning process. This study recommends that teachers consider incorporating mind mapping into their teaching practices to improve the quality of reading comprehension among students in SD/MI.